CODESRIA Bulletin Online, No. 1, January 2023 - The Globalisation of Football is Closing Performance Gaps among Countries in the World Cup - Bangura, Yusuf (CODESRIA Bulletin, 2023)
The 2022 Qatar World Cup has been hailed as the best in the tournament’s ninety-two-year history, producing moments of magic and upset, nail-biting finishes and amazing goals. This World Cup will also be remembered for signalling a serious challenge by African, Asian and North/Central American teams to football’s dominance by teams from Europe and South America—the two regions that created the tournament in 1930 and have dominated it since its inception. Despite the two finalists in 2022 (Argentina and France) being European and South American teams, the World Cup is on the cusp of becoming a truly global competition in which teams from other regions have a fair chance of winning it. Qatar 2022 has shown that there is a clear narrowing of the performance gap between countries. Gone are the days when many teams from Africa and Asia suffered heavy defeats or were mostly eliminated at the group stage of the competition. The globalisation of football, which allows players, managers and money to flow freely across football leagues around the world, accounts largely for the closing gap in football standards. European and South American Dominance[1] Europe and South America have enjoyed the lions’ share of participation slots for most of the tournament’s history. Partly, this was due to the colonial status of much of Africa and Asia during the formative stage of the tournament and the late development of football in the two regions. Indeed, it is debatable whether the eight World Cups of 1930–1966 should be classified as World Cups because of the extremely limited or zero participation by these regions. Prior to 1970, there were no guaranteed slots for every region or football confederation. In fact, in 1930, participation was by invitation and only thirteen countries took part in the tournament. Hosted by Uruguay, the 1930 World Cup was largely a tournament for South America, which had seven teams; Europe (four teams) and North/Central America (two teams) shared the remaining slots. No African or Asian team played in the tournament. Europe asserted its dominance of the World Cup in 1934 when Italy played host, claiming twelve of the sixteen slots, with South America (two), the USA (one) and Egypt (one) sharing the rest. No Asian team was represented. The 1938 tournament in France repeated the 1934 Eurocentric pattern, with Europe getting thirteen slots, South America two and Asia one. There was no African team. South America readjusted the European-South American imbalance of 1934 and 1938 in 1950, when Brazil hosted the tournament, with five slots allocated to South America, six to Europe and two to North/Central America. Africa and Asia were not represented. Again, there were only thirteen teams in the tournament. On the Europe–South America axis, Uruguay, Brazil, Argentina, Italy and France stood out as the dominant countries, with France’s Jules Rimet, FIFA’s third president, playing a leading role in initiating the tournament. Interestingly, since Euro 1996, England likes to see itself as the home of the World Cup, with the song ‘It’s coming home’ becoming an English fan anthem in every World Cup tournament. What the fans may not know is that England started competing in the World Cup only in 1950. It did not feature in the founding tournament and boycotted the 1934 and 1938 tournaments, both of which it regarded as inferior to its own four-nation British International Championship of England, Scotland, Wales and Northern Ireland. The absence of African and Asian teams, or participation of only one team from both regions (which were treated as a single group), continued until 1970 when for the first time in the tournament’s history both Africa and Asia were guaranteed one slot each. Africa and Asia increased their share of participation to two each in 1982 when the number of teams in the competition was raised from sixteen to twenty-four. However, the new format reinforced Europe’s dominance, giving it an average of fourteen slots (58 per cent) in each tournament up to 1994. South America’s slot was pegged at three to four (12.5 per cent–16.6 per cent). It is important to note that Europe and South America already had football tournaments or leagues as far back as the nineteenth century. So football was more advanced in those two regions than in Africa and Asia. The prevailing view was that allocating the slots on the basis of population or number of teams in a confederation would considerably dilute the quality of the game. Africa and Asia had to earn more spots by improving the quality of their football. FIFA used two criteria to allocate tournament slots: the number and quality of the teams in each confederation. Even before the globalisation of football, Africa was already making progress based on these criteria. In the 1994 tournament, the last time the twenty-four-team format was used, Africa was given an extra slot, bringing its share to three—half a point less than South America, which has fewer teams in its confederation than Africa. Asia’s share was still pegged at two even though an Asian team (North Korea) beat a European team (Italy) in the 1966 tournament. By the 1990s, African, Asian and Central American-Caribbean football federations had become active members of FIFA and accounted for the majority of the organisation’s membership. The clamour for more slots for non-European/South American teams increased, leading to the current thirty-two-team format that was adopted in 1998. Africa’s share increased to five, Asia’s to 3.5 and South America’s remained the same (four). Importantly, Europe’s share fell from 58 per cent in 1994 to 43.75 per cent in 1998. In 2026, when a forty-eight-team format will be implemented, Europe’s share will decline further to 33.3 per cent (sixteen slots). Africa will have 9.3 slots (19.3 per cent) and Asia 8.3 (17.3 per cent). Turning Parity in Participation into Good Performance Outcomes The struggle for parity in participation did not immediately lead to a narrowing of the gap between Europe/South America and the other regions. In the first three World Cups that followed the allocation of single slots to Africa and Asia (1970, 1974 and 1978), no African or Asian team won a match or went beyond the first group stage. Africa’s first positive impression was in 1982, even though—as in 1978—no team got out of the first group stage. Cameroon drew in all its three group-stage matches and Algeria beat West Germany and Chile but failed to qualify for the second group stage because of collusion between West Germany and Austria, in which both teams limited the number of goals Germany would score against Austria in their final group match. The three teams ended with four points each and Algeria was eliminated on goal difference. It was this disgraceful act that prompted FIFA to schedule the final games of all teams in each group at the same time in subsequent tournaments. And in 1986, Morocco became the first country outside Europe and the Americas to qualify for the Round of 16 by beating Portugal and drawing with England. Africa’s big breakthrough was in 1990, when Cameroon topped its group at the group stage, scaled through the Round of 16 and qualified for the quarter-finals. Asia had a bad World Cup that year, as its two representatives—South Korea and the United Arab Emirates—failed to win a single point at the group stage. Africa’s second representative, Egypt, also failed to get beyond the group stage. In the 1994 tournament, the Nigerian team, which had a bucketful of highly skilled players plying their trade in European leagues, put down a marker by topping its group and playing attractive, attacking football, but went out to Italy in the Round of 16. After Cameroon’s brilliant performance in 1990 and Nigeria’s swashbuckling display in 1994, many pundits believed that Pelé’s prediction in 1977 that an African team would win the World Cup before the end of the twentieth century would be realised easily. The only other tournaments in which an African or Asian team qualified for the quarter-finals before Qatar were in 2002, when South Korea went as far as the semi-finals and Senegal reached the quarter-finals, and 2010, when Ghana qualified for the quarter-finals. Ghana was minutes away from qualifying for the semi-finals but a goal-bound shot was flagrantly handled on the touchline and stopped from entering the net by the Uruguayan striker, Luis Suarez, and the Ghana striker, Asamoah Gyan, missed the awarded penalty. The overall performance of African and Asian countries in World Cup tournaments before 2022 was one of few peaks, which rose above quarter-final level on only two occasions. Most teams often failed to get out of the group stage. One way of assessing the progress that African and Asian teams have made in the World Cup is to examine their performance between 1970 (when they were first given guaranteed slots) and 2022, focusing on the number of times African and Asian teams qualified from the first group stage or appeared in the Round of 16. Four African and Asian teams participated in the quarter-finals and two in the semi-finals. As Table 1 shows, before 2022, three Asian and African teams qualified for the Round of 16 only twice—in 2002 and 2010. In three tournaments (1970, 1974 and 1978), no team from those two regions got out of the group stage. In five other tournaments (1986, 1990, 1998, 2006 and 2018) only one team featured in matches beyond the first group stage. And only two teams qualified in 1994 and 2014. In 2022, however, five African and Asian teams made it to the Round of 16. This is all the more remarkable as only one or two teams qualified in 2014 and 2018. Indeed, the 2022 Qatar tournament was the only time a team from every regional football confederation was represented in the Round of 16. The competitive nature of the 2022 World Cup is sharply evident when we examine the number of third-place teams in the group stage that won four points between 1998 (when the thirty-two-team format was introduced) and 2022. In the previous six tournaments, it was only in 2010 that five third-place teams won four points. In 2002, four teams got four points, but in the remaining tournaments only one or two fourth-place teams secured four points. In contrast, in the 2022 tournament seven fourth-place teams received four points. Two African teams (Cameroon and Tunisia) were among the seven teams that placed third with four points, suggesting that they narrowly missed qualifying for the Round of 16. The least-performing African team, Ghana, got three points. The worst-performing teams in the tournament—Qatar, Canada, Denmark and Serbia—scored zero or one point. Qatar 2022 was a good tournament for Africa. The Qatar tournament was, indeed, highly competitive. After two matches in the group stage, only three teams qualified for the Round of 16 and only two teams were eliminated. Thus, twenty-seven teams battled for thirteen of the sixteen slots in the final matches of the group stage. It is not surprising that these matches produced some of the most thrilling games in the tournament. African, Asian and North/Central American teams were well represented in those matches. The most memorable were the Germany–Costa Rica and Japan–Spain matches in Group E; Croatia–Belgium and Canada–Morocco matches in Group F; Ecuador–Senegal and Netherlands–Qatar matches in Group A; Argentina–Poland and Mexico–Saudi Arabia matches in Group C; and Ghana–Uruguay and Portugal–South Korea matches in Group H. Table 1: Number of African and Asian teams in post-group stage/Round of 16 matches Source: FIFA and Wikipedia reports on the results of World Cup matches. The Germany–Costa Rica and Japan–Spain matches in Group E will live on in the memory. For Germany to go through this stage, it needed Spain to beat Japan or at least force a draw, and Germany needed to beat Costa Rica. Germany played its own part by beating Costa Rica, but the goal difference was not enough to lift Germany out of the group. Japan scored a technology-sanctioned goal in the fifty-first minute to lead Spain and dash Germany’s hopes of qualifying. The base of the ball was out of play but part of the ball’s circumference was on the touchline. At one point both Germany and Spain were going out, as Costa Rica led Germany 2–1 in the seventieth minute. However, Germany saved Spain by equalising against Costa Rica in the seventy-third minute. Germany kept pushing for more goals to overtake Spain if Spain failed to beat Japan, while at the same time hoping that Spain would equalise against Japan and put Germany in second place behind Spain and ahead of Japan. It is difficult to think of a similar drama in previous tournaments when a team pursued contradictory preferences to qualify for the next round. In the end, Germany couldn’t get the required number of goals and Spain couldn’t equalise against Japan. Germany’s 4–2 victory only helped Spain to qualify, with Japan, for the next round. Qatar 2022 was also noted for large-scale upsets, which are a good measure of the competitiveness of a football tournament. Football analysts define an upset as a match in which a team with lower odds wins. Using data on team odds from the website oddsportal, The Economist (9.12.2022) examined the odds and results for all matches in all stages of World Cup competitions between 2002 and 2022. It found that five of the ten least-probable results in the six tournaments between 2002 and 2010 occurred in Qatar. Remarkably, European and South American teams were beaten twelve times by African and Asian teams in the Qatar World Cup. This is the same number of times that European and South American teams beat African and Asian teams. The most spectacular African and Asian victories were Morocco’s defeat of three European football giants (Belgium, Spain and Portugal), Saudi Arabia’s defeat of Argentina, and Japan’s victory over Spain and Germany. We could also add Cameroon’s defeat of Brazil and Tunisia’s victory over France, even though these were dead rubber games. Qatar 2022 also had more penalty shootouts than any other World Cup. Penalty shootouts, which occur when no team emerges as winner after 120 minutes of play in the knockout stages, were introduced in the 1978 World Cup. They can be used to measure the competitiveness of tournaments. As Figure 1 shows, there were five penalty shootouts at the Qatar World Cup, the highest number since its introduction. Figure 1: Number of World Cup matches ending in a penalty shootout. Source: Extracted from FIFA and Wikipedia documentation of results of World Cup matches. The Globalisation of Football Qatar 2022 clearly shows that it is no longer a given that teams from Europe and South America will routinely beat teams from Africa and Asia in World Cup tournaments. The chances of African and Asian teams advancing far into World Cup tournaments have increased substantially. What accounts for this turn of events? The answer surely lies in the globalisation of football, with European leagues becoming the epicentre where most good players in the world play. As Branko Milanovic (2003) has observed, using an economics model, which assumes increasing returns to scale, the free movement of players leads to a concentration of the best players in the same club or league; this improves the quality of those players exponentially as the best players play with others who are also among the best. As recently as 1992, when the English Premier League was formed, there were only thirteen foreign players in the English league—mostly from other European countries and a few from Argentina. The European Community lifted the ban on foreign players in Europe’s leagues in a landmark ruling in 1978, but a few obstacles remained and very few footballers from Africa, Asia and Latin America took advantage of the ruling to play in Europe. Football was still a national game, played by national players, managed by national coaches and funded by national money. However, the liberalisation of the international transfer market in 1995, which allows players to move freely across leagues at the end of their contracts without financial jeopardy, led to a rapid transformation of the European leagues. Out of the 502 players registered in the Premier League today, 329 (65 per cent) are foreign. The 2016 CIES Football Observatory Monthly Report shows that European leagues recruited on average about 48 per cent of their players from foreign countries. Even leagues in other regions, such as Asia and Latin America, increasingly rely on foreign players. By 2016, almost half of the players in the USA’s Major League Soccer were foreign. In the Premier League, Aston Villa was the last club to field an all-English team—in 1999; and in 2005, Arsène Wenger’s Arsenal became the first club to field an all-foreign team (including substitutes) (Football Stadiums n.d.; The 1988 Letter 2022). African, Latin American and Asian players form a substantial portion of the foreign players in foreign leagues. The 2020 CIES Football Observatory Report estimated that, in 2019, Brazil had the highest number of players in foreign leagues—1,535 players. Four South American countries (Brazil, Argentina, Colombia and Uruguay) were in the top twenty countries with players in foreign leagues. Interestingly, four African countries (Nigeria, Senegal, Ghana and Côte d’Ivoire) were also in the top twenty. A KPMG study in 2021 (“The African Power in Europe”) showed that more than 500 African footballers played in eleven major European leagues selected for the study. The top ten countries of these players by order of importance were Senegal, Morocco, Nigeria, Côte d’Ivoire, Ghana, Algeria, Mali, Cameroon, DR Congo and Guinea. The free movement of players across leagues has also impacted on the recruitment of managers. The Premier League led the way, with 65 per cent of managers recruited overseas by 2019. Foreign managers were still substantially in the minority in the other four top leagues in Europe—30 per cent in Ligue 1, 25 per cent in La Liga, 18 per cent in the Bundesliga and 5 per cent in Series A (CGTN, 2018). But the key point is that, even in these leagues, the idea of restricting recruitment of managers to those who plied their trade in national leagues was becoming untenable. The free movement of players and managers is underpinned by the liberalisation of club ownership, from communities to private investors. This has transformed football into a mega transnational business. For context, when the Premier League was formed in 1992, it had a revenue of only GBP 170 million (USD 257 million). Today it is the richest league in the world with a revenue of about USD 9 billion, followed by La Liga with USD 5 billion, Series A with USD 4.8 billion, the Bundesliga with USD 4.2 billion and Ligue 1 with USD 3.9 billion (Ganzallo 2022). The Premier League is at the top of the revenue pyramid because it is financially attractive and the most liberal in granting ownership to foreign investors: 75 per cent of the clubs in the Premier League are owned by foreigners. The Bundesliga’s 50+1 rule, in which 50 per cent of a club’s shares are reserved for members, restricts foreign ownership. The top La Liga clubs are owned by members, or socios; however, foreign money is now present in some of the other clubs, such as Espanyol de Barcelona, Atletico Madrid, Granada and Valencia. Ligue 1 has also attracted foreign investors, with Paris Saint-Germain topping the list. Football Benchmark 2020 reports that there have been fifteen foreign-majority buy-ins, although most are at relatively low amounts, of EUR 10–20 million (USD 10.6–22 million). Family ownership of clubs is the norm in Series A; however, five clubs are now owned by foreign investors. Statistica (2018) reports that by 2018, 46 per cent of Europe’s, 25 per cent of North America’s and 21 per cent of Asia’s leagues were owned by foreigners. Broadcasting revenue and sponsorship or commercial deals, which far outweigh matchday revenues, account for the lion’s share of club revenues. The Premier League’s foreign broadcasting revenue now accounts for 40 per cent of total broadcasting revenue, making global audiences a critical part of the English league’s football landscape. Foreign finance and foreign audiences have given the Premier League a formidable lead over other leagues, facilitating the recruitment of top players and managers from all over the world. With 65 per cent of both its players and managers recruited from foreign countries and 75 per cent of its clubs owned by foreigners, the Premier League is, indeed, the quintessential globalised league in the world. The Effects of Globalisation The globalisation of football has had two major effects on the World Cup. Firstly, most of the players from the teams that excel in the tournament play in European leagues and are exposed to the same systems of play. Surely, the pull of Europe in global football deprives leagues in Africa, Asia and the Americas of top talent. However, nations with weak or non-existent leagues benefit substantially from the exposure of their players to the techniques, tactics, rigour and discipline of top-flight European leagues. As Table 2 shows, the overwhelming majority of the players in the twenty-six-man squads of Cameroon, Ghana, Senegal and Morocco play in Europe. Indeed, all the players in Senegal’s squad play for European clubs. Only Tunisia in the Africa group has a large number of players recruited from its domestic league. But even in this case, players from the domestic league account for only 34.6 per cent of the squad; those from European leagues account for 42 per cent. Asia’s integration into European league football is not as high as Africa’s, but even in that region a good number of players play in Europe: 76 per cent from Japan, 57.6 per cent from Australia, 53.8 per cent from South Korea and 48 per cent from Iran. Only the Saudi Arabia and Qatar teams fielded no player from a European league. The entire Saudi Arabia squad comprises home-based players and twenty-five of Qatar’s twenty-six players are from the national league. Both Saudi Arabia and Qatar were eliminated in the group stage in Qatar 2022. I’ve included in Table 2 Brazil and Argentina, the two top teams in South America, with a combined total of eight World Cup trophies and thirteen appearances in World Cup finals, to demonstrate the powerful pull of Europe in global football today. In the 1960s and 1970s, South American clubs were highly competitive against European clubs. Brazil’s Santos, led by Pelé, was even better than most of the top European teams. As champions of South America, Santos won the Intercontinental Cup in 1962 against Benfica, which was the champion of Europe. And out of the 124 matches that Santos played against European clubs during Pelé’s time, Santos won ninety, drew twenty and lost fourteen (Gregoriak 2002). Unfortunately, the quality of Brazilian, indeed South American, club football today leaves much to be desired as most of the best players now play in Europe. As Table 2 shows, twenty-five out of the twenty-six players of Argentina’s squad for the Qatar World Cup, and twenty-two of Brazil’s, play in Europe. It is not surprising that FIFA’s Club World Cup tournaments have failed to excite the football world. European clubs play against far weaker opponents and most often win. The last time a non-European team (Corinthians of Brazil) won was in 2012. The second effect of globalisation is the ease with which the standardisation of the methods of play in European football has improved the techniques of players from regions without a strong football tradition. The Brazilian/South American free-flowing, individualistic and joyful style of play (joga bonito), which is learned in futsal (five-a-side matches in small spaces) or street football, has given way to systems-based approaches in which managers enjoy tremendous power to influence formations and tactics. The rise of European football academies helps to drill these techniques into players at an early age. Individual flair or creativity, such as Richarlison’s juggling of the ball on his head three times like a seal before initiating the passes that led to Brazil’s third goal against South Korea in the Qatar tournament, may be seen as showboating or time-wasting by football managers. That goal was the most beautiful in the tournament. Only a player from Brazil or South America could have conjured it. Table 2: Foreign and domestic league players in African and Asian teams Source: Various news reports on the World Cup squads of the 32 country teams that played in Qatar. With so much money in the game, winning has become the overriding goal and it is the job of managers to enforce it. The master of systems-based football, Pep Guardiola, is fond of saying that his job is to get his players to move the ball to the final third of the pitch, which is the only area where players are given the freedom to be inventive in trying to score goals. In other words, play in two-thirds of the pitch must follow the instructions of the manager. A standardised, systems-based style of play is much easier to learn and replicate than one based on individual skill, intuition or improvisation. It mimics capitalism’s standardisation and mechanisation of production, which destroyed the creativity of traditional craftsmanship or artistry in many societies. The owners and administrators of capital can now use well-tested templates to quickly replicate systems of production everywhere. This is not to berate systems-based methods of play. With highly gifted players, as Guardiola was lucky to assemble at Barcelona between 2008 and 2012, touch-the-ball, pass-the-ball, or one-touch tiki taka football can be a joy to watch. That team played the best club football I have ever seen. Some of the most popular football formations today are 4-3-3, 3-4-3, 4-4-2, 4-5-1, 3-5-2, 5-3-2 and 5-4-1. These may indicate whether a team is adopting a defensive or attacking approach. Tactics may include the Dutch team’s total football in the 1970s under Rinus Michels in which any player can be a striker, a midfielder or a defender, depending on the flow of the game; the possession-based, one-touch football or tiki-taka, perfected by Barcelona; the high press, or Gegenpressing, of German teams; the high press and quick transitions of Jürgen Klopp’s Liverpool; the counterattack; the use of a false striker rather than a real centre-forward, perfected by Manchester City’s Pep Guardiola; the kick-and-rush tactics as well as long balls of traditional English teams; the highly defensive catenaccio tactic of Italian football; and parking-the-bus in which most of the players remain in their own half and frustrate superior opponents from scoring—made famous by José Mourinho. Underpinning these tactics is mastery of the basics of the game. These include knowing how to control and pass a ball; making laser-sharp long crosses; defending corner kicks; setting or avoiding offside traps; committing professional fouls to frustrate goal-bound attacks; close marking of predatory strikers; and avoiding errors that can lead to penalties. Most teams in Qatar got the basics right. However, non-European/South American teams have struggled in the past to master these basic skills. For instance, Zaire’s team in the 1974 World Cup conceded nine goals against Yugoslavia, many through set pieces or corners and naive defending. Conclusion: Can a team from Africa, Asia, and North/Central America win the World Cup? Despite globalisation, the World Cup has been won by only eight countries—five European (Germany, Italy, France, Spain and England) and three South American (Brazil, Argentina and Uruguay). And a non-European/South American country has been in the semi-finals only twice. However, as we have seen, African and Asian teams are now competitive at the group stage and Round of 16. With globalisation and the mastery of the basic skills, formations and tactics of the game, it may not be long before an African, Asian or North/Central American team wins the tournament. In my concluding remarks I will focus largely on Africa’s chances, some of which may apply to the other regions. African countries may have to ramp up investment in, and administration of, their leagues and football academies in order to improve the quality of the game in domestic settings and create a seamless transition between playing in national leagues and playing overseas, especially if they are to attract the large number of foreign-born Africans who opt to play for European teams. Morocco’s team had the largest number of foreign-born players (fourteen) at the Qatar World Cup, followed by Tunisia and Qatar (twelve each). Cameroon (nine) and Ghana (eight) also had a sizeable number of foreign-born players (Santamaria and Fusco 2022). The key issue is how to attract the super-elite diaspora players who are quickly snatched by the football federations in the European countries of their birth. Morocco seems to have developed a good model for nurturing national talent and attracting elite-level Moroccan players born overseas. Top foreign-born players, like Achraf Hakimi, Hakim Zyech and Sofiane Boufal, who play in Europe’s top-flight leagues, are scouted and incentivised by Moroccan authorities at an early age before they qualify and are tempted to play for the national team of the country of their birth. Developing strong ties with diaspora players makes it easier for such players to opt to play for their country of origin. The Moroccan government also built a first-class academy, the Mohammed VI Football Academy, to attract and nurture local talent. Some of the products of this academy often move to European leagues and, if they are successful, are recruited into the Morocco national team. The team in Qatar had four graduates from the Mohammed VI Academy (Trend news detail. https://news.trenddetail.com/news/295892.html). Morocco stands a better chance than other African countries to get to the final of a World Cup and maybe win it. A Morocco team (Wydad AC) is the current holder of the Confederation of African Football’s Champions League trophy. One drawback that African and other non-European/South American teams faced in Qatar 2022 was the dearth of clutch players, especially at the midfield and forward positions. Mastering the basic skills and tactics of football may allow countries to narrow the performance gap with Europe and South America but may not be enough to get teams over the line. As the gap in standards gets smaller, outcomes are decided by small margins, which may depend on experience and having difference-making players like an Mbappé, a Messi, a Neymar and a Benzema, who can change the trajectory of games and win them. Most World Cup winning teams have such players. Africa has had many clutch players, such as Roger Milla, Samuel Eto’o, Patrick Mboma, Didier Drogba, Jay Jay Okocha, Mustapha Hadji, Nwankwo Kanu, George Weah, Abedi Pele, Mohammed Salah, Sadio Mané, Yaya Touré and Rigobert Song. Africa and other regions need to produce these kinds of highly skilled, swashbuckling players with a winning mentality if the catching-up process is to yield the ultimate prize. References CGTN, 2018, Premier League has most international managers among major soccer leagues, CGTN.COM, 28 July 2018. https://news.cgtn.com/news/3d3d414e7745544d79457a6333566d54/share_p.html CIES Football Observatory Monthly Report, 2016, Foreign players in football teams, Issue 12, February. https://www.football-observatory.com/IMG/sites/mr/mr12/en/ CIES Football Observatory Monthly Report, 2020, Football players’ production index: measuring nations’ contributions, No. 55, May. https://www.football-observatory.com/IMG/pdf/mr55en.pdf Football Benchmark 2020, (25.02.2020), ‘Foreign Investors in European Football—Can Italy Become The Next Preferred Target?´ https://www.footballbenchmark.com/library/foreign_investors_in_european_football_can_italy_become_the_next_preferred_target Football Stadiums (n.d.), Foreign Players in the English Game. https://www.football-stadiums.co.uk/articles/foreign-players-in-football/ Ganzallo, S., 2022, These Are The 10 Most Valuable Football Leagues In The World, The Richest, 2 July 2022. https://www.therichest.com/rich-powerful/these-are-the-10-most-valuable-football-leagues-in-the-world/ Gregoriak, 2002, “Pele`s Santos vs. European Clubs - Statistical Overview”. https://www.bigsoccer.com/threads/pele-s-santos-vs-european-clubs-statistical-overview.157423/ KPMG, 2021, The African Power in Europe, Football Benchmark, 23 November 2021. https://www.footballbenchmark.com/library/the_african_power_in_europe Milanovic, B. 2005, “Globalization And Goals: Does soccer show the way?”, Review of International Political conomy. Vol. 12, Issue 5. Santamaria, C and P, E. Fusco 2022, “The graphic truth. The World Cup of immigration”. GZERO. 2 December Statistica. “Number of foreign owners of top division top football clubs in Europe in 2018, by origin”. https://www.statista.com/statistics/894012/foreign-ownership-of-football-clubs-europe-by-origin/ The 1998 Letter, Football Then and Now, 29.10.2022, Foreign Players in the Football League. https://the1888letter.com/foreign-players-football-league-introduction/ The Economist, 9.12.2022, Qatar’s World Cup has seen the biggest upsets in recent history. https://www.economist.com/graphic-detail/2022/12/09/qatars-world-cup-has-seen-the-biggest-upsets-in-recent-history Trent news detail. https://news.trenddetail.com/news/295892.html [1] The data for the analysis of the dominance of Europe and South America in the allocation of World Cup participation slots is extracted from accounts of each tournament by FIFA and Wikipedia.